2022
DOI: 10.3390/educsci12030203
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Encounters with the Built Environment as the Basis for Urban Environmental Education

Abstract: As the majority of people in the world now live in cities, it makes sense to question the state of urban environmental education and how it could be developed going forward. In this article, we suggest a way forward based on the essays written by Finnish university students. The students reflected on their relationship with an environment that is meaningful to them. In the essays selected for this case study (n = 25), the built environment of Helsinki—the capital of Finland—and its characteristics are in focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…They thus had to deal with problems in the real world by collecting and interpreting data and reflecting on the evidence to reach conclusions, develop curiosity, and to ask themselves further questions, as suggested in the studies by Minocha et al [62], and Pederson and Irby [25]. Thus, critical thinking is stimulated and people are prepared to participate effectively and constructively in social life through reflection, real-world problem solving, and emotional management [63]. Moreover, participants positively valued the usefulness of the sound and visual landscape for the development of social and environmental teaching competences [64], highlighting that it promotes the approach to nature and environmental commitment [16,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They thus had to deal with problems in the real world by collecting and interpreting data and reflecting on the evidence to reach conclusions, develop curiosity, and to ask themselves further questions, as suggested in the studies by Minocha et al [62], and Pederson and Irby [25]. Thus, critical thinking is stimulated and people are prepared to participate effectively and constructively in social life through reflection, real-world problem solving, and emotional management [63]. Moreover, participants positively valued the usefulness of the sound and visual landscape for the development of social and environmental teaching competences [64], highlighting that it promotes the approach to nature and environmental commitment [16,58].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between sounds and health is shown by the emotions perceived when experiencing the soundscape, showing the importance of using the acoustic environment as an educational resource for health and environmental education, as it focuses on the associated problems and acoustic contamination. The problems of acoustic contamination are analyzed from the perspective of urban environmental education; therefore, it is important to pay attention also to the social and cultural aspects, and not only to the ecological dimension [63]. The experience showed that the listening technique can be used as a teaching resource in interpreting the soundscape and that a type of "ear-cleaning" is required to improve our hearing capacity and discriminate clearly between the different elements as a technique that helps us to understand the sounds in the environment and their components.…”
Section: Discussionmentioning
confidence: 99%
“…Students can interact with one another in the social environment. An environment that is very close to students is a part of the social environment [16]. As a result, making use of the social environment can be an alternative learning strategy that fits the needs of elementary school students.…”
Section: Introductionmentioning
confidence: 99%